Carcass Quality, Non-Carcass Component and Meat Cholesterol of Kacang Goat Fed with Fermented Cocoa Shell - Edi Suryanto; Bulkaini Bulkaini; Soeparno Soeparno; Mastur Mastur (Buletin Peternakan, 2018)
The experiment was conducted to investigate carcass quality, non-carcass component and meat cholesterol content of Kacang goat fed with fermented cocoa shell (FCS). Materials used in the experiment consisted of 9 male Kacang goat (6 - 9 months of age and ± 18,67 kg of body weight), corn straw, rice bran and FCS using three types of starters. The goat was divided into 3 groups of FCS fermentation of cocoa shell were carried out using 3 types of starters, i.e. cocoa shell fermentation 1) without additional starter (WAS FCS), 2) with Bioplus (Bioplus FCS, 3) with burger feed sauce (BFS FCS). All goats were fed corn straw and rice bran amounting to 70% and FCS amounting to 30% for 2 months. They were then slaughtered at Majeluk Slaughterhouse, Lombok. The data of carcass quality, non-carcass component, cholesterol content, and marbling were collected. The results showed that the carcass quality and non carcass component of Kacang goat were not significantly different among the feed treatments. However, the cholesterol content of meat was significantly different among the feed treatments (P<0.05). The average of carcass percentage, backfat thickness, rib eye area, fleshing index, cholesterol content and marbling of Kacang goat fed WAS FCS were 47.69%, 1.68 mm, 29.01cm2, 0.85%, 30.13 mg/100g, and 0.16%; fed Bioplus FCS were 48.67%, 1.80 mm, 30.79 cm2, 0.91%, 34.96 mg/100g and 0.05%; fed BFS FCS were 48.02%, 1.74 mm, 29.90 cm2, 0.77%, 31.88 mg/100g, and 0.11%, respectively. Non-carcass component of Kacang goat was not significantly different among the feed treatments, it was 42.41±0.064% in average. Cholesterol content of meat of Kacang goat differed among the feed treatments (P<0.05). Kacang goat fed WAS FCS had the lowest cholesterol content (30.13 mg/100 g). It could be concluded that Kacang goat fed ration containing fermented cocoa shell with several starters produced similar carcass quality and non carcass component. However, FCS without additional starter resulted in lower cholesterol content of meat.